Anticholinesterase Activity of Eight Medicinal Plant Species: In Vitro and In Silico Studies in the Search for Therapeutic Agents against Alzheimer's Disease. (25th June 2021) - Uddin, Md Josim; Russo, Daniela; Rahman, Md Mahbubur; Uddin, Shaikh Bokhtear; Halim, Mohammad A.; Zidorn, Christian; Milella, Luigi
Abstract : Many Bangladeshi medicinal plants have been used to treat Alzheimer's disease and other neurodegenerative diseases. In the present study, the anticholinesterase effects of eight selected Bangladeshi medicinal plant species were investigated. Species were selected based on the traditional uses against CNS-related diseases. Extracts were prepared using a gentle cold extraction method. In vitro cholinesterase inhibitory effects were measured by Ellman's method in 96-well microplates. Blumea lacera (Compositae) and Cyclea barbata (Menispermaceae) were found to have the highest acetylcholinesterase inhibitory (IC50, 150 ± 11 and 176 ± 14 µ g/mL, respectively) and butyrylcholinesterase inhibitory effect (IC50, 297 ± 13 and 124 ± 2 µ g/mL, respectively). Cyclea barbata demonstrated competitive inhibition, where Blumea lacera showed an uncompetitive inhibition mode for acetylcholinesterase. Smilax guianensis (Smilacaceae) and Byttneria pilosa (Malvaceae) were also found to show moderate AChE inhibition (IC50, 205 ± 31 and 221 ± 2 µ g/mL, respectively), although no significant BChE inhibitory effect was observed for extracts from these plant species. Among others, Thunbergia grandiflora (Acanthaceae) and Mikania micrantha (Compositae) were found to display noticeable AChE (IC50, 252 ± 22 µ g/mL) and BChE (IC50, 314 ± 15 µ g/mL) inhibitory effects, respectively. Molecular docking experiment suggested that compounds 5-hydroxy-3, 6, 7, 3′, 4′-pentamethoxyflavone (BL4) and kaempferol-3- O - α -L-rhamnopyranosyl-(1⟶6)- β -D-glucopyranoside (BL5) from Blumea lacera bound stably to the binding groove of the AChE and BChE by hydrogen-bond interactions, respectively. Therefore, these compounds could be candidates for cholinesterase inhibitors. The present findings demonstrated that Blumea lacera and Cyclea barbata are interesting objects for further studies aiming at future therapeutics for Alzheimer's disease.